2010
DOI: 10.1038/onc.2010.480
|View full text |Cite
|
Sign up to set email alerts
|

Methyltransferases mediate cell memory of a genotoxic insult

Abstract: Characterization of the direct effects of DNA-damaging agents shows how DNA lesions lead to specific mutations. Yet, serum from Hiroshima survivors, Chernobyl liquidators and radiotherapy patients can induce a clastogenic effect on naive cells, showing indirect induction of genomic instability that persists years after exposure. Such indirect effects are not restricted to ionizing radiation, as chemical genotoxins also induce heritable and transmissible genomic instability phenotypes. Although such indirect in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 51 publications
5
26
0
Order By: Relevance
“…In some cases, however, IR-induced delayed reproductive death may depend on heritable effects not requiring DNA breakage (22). Effects that have been proposed in this regard include altered gene expression resulting from aberrant DNA cytosine methylation (23), centrosome amplification leading to multipolar mitosis (24), and self-sustaining production of hydrogen peroxide and elevated oxidative stress associated with mitochondrial dysfunction (25). Indeed, the question of how IR kills cells, with its important implications for radiotherapy, is a matter of continuing debate (26,27).…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, however, IR-induced delayed reproductive death may depend on heritable effects not requiring DNA breakage (22). Effects that have been proposed in this regard include altered gene expression resulting from aberrant DNA cytosine methylation (23), centrosome amplification leading to multipolar mitosis (24), and self-sustaining production of hydrogen peroxide and elevated oxidative stress associated with mitochondrial dysfunction (25). Indeed, the question of how IR kills cells, with its important implications for radiotherapy, is a matter of continuing debate (26,27).…”
Section: Resultsmentioning
confidence: 99%
“…There is also evidence of possible involvement of indirect, untargeted interactions between cells and complex cytokine-like signal transduction processes [42, 5961]. Rugo et al [62] demonstrated the role of methylation in the transmission of GI in embryonic stem cells by showing that the elimination of DNA cytosine methylation genes, Dmmt1 and Dmmt3a , completely eliminated transmission of GI. Ilnytskyy and Kovalchuk [63] presented further evidence on the role of methylation and miRNA- short RNA molecules in eukaryotic cells that regulate gene expression [64] in radiation-induced GI and BE.…”
Section: Types Of Non-targeted Effectmentioning
confidence: 99%
“…CIN in bone marrow has been demonstrated in vivo after 1 or 3 Gy total body low- linear energy transfer [62] irradiation. However, at lower doses of 0–0.5 Gy there was no evidence of CIN [76].…”
Section: Types Of Non-targeted Effectmentioning
confidence: 99%
“…This hinted that radiation hormesis could be related to hypermethylation upon low-dose IR exposures [128]. As regards non-targeted effects, Rugo et al [131] studied the effects of the irradiated cell conditioned medium (ICCM) on unirradiated cells. Interestingly, through comet analysis, inactive DNMT1 in mice ES cell could protect neighboring cells from indirect induction of genomic instability [131].…”
Section: Epigenetic Effects Of Ionizing Radiationmentioning
confidence: 99%